Labor Market Hardships and Preferences for Public Sector Employment and Employers: Evidence from Russia - Olivia Jin; William Pyle (Center for Economic Studies and ifo Institute (CESifo), 2021)
A growing literature connects labor market hardships to stronger preferences for government welfare and redistribution programs. Potential preference shifts with respect to other types of state involvement in the economy, however, have gone unexplored. We draw on both longitudinal and pseudo-panel data from Russia to explore how labor market hardships relate to preferences for public sector employment and employers. In fixed effects specifications, we demonstrate that feelings of job insecurity, experiences with wage arrears, and spells of unemployment all increase the attractiveness of work in the public sector. Pseudo-panel data provide only mixed evidence as to whether such effects endure over the longer run.
Keywords: H10; J45; J60; P35; 330; economic shocks; personal experience; public employment; political preferences